2010
DOI: 10.1111/j.1740-8784.2010.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

GuanxiDynamics and Entrepreneurial Firm Creation and Development in China

Abstract: Guanxi networks are critical for achieving entrepreneurial success in China. Informed by the literatures on network‐based entrepreneurship and guanxi, this study used a multiple‐case method to examine the development of Chinese entrepreneurs' guanxi networks in the entrepreneurial process. Data induction based on within‐ and cross‐case analyses of six entrepreneurial firms revealed three major findings. First, guanxi network dynamics in terms of network structure, governance mechanisms, and network content cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
156
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(159 citation statements)
references
References 59 publications
3
156
0
Order By: Relevance
“…Furthermore, they suggested that guanxi can be regarded as a strategic tool which can increase the efficiency and effectiveness of doing business in China. In the field of entrepreneurship, Guo and Miller's (2010) [2] work suggested that guanxi connections play a significant role across entrepreneurial processes. First, during firm creation, guanxi ties with family members and relatives may provide initial funding or psychological support for entrepreneurs [4].…”
Section: Guanxi Strategy Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they suggested that guanxi can be regarded as a strategic tool which can increase the efficiency and effectiveness of doing business in China. In the field of entrepreneurship, Guo and Miller's (2010) [2] work suggested that guanxi connections play a significant role across entrepreneurial processes. First, during firm creation, guanxi ties with family members and relatives may provide initial funding or psychological support for entrepreneurs [4].…”
Section: Guanxi Strategy Theorymentioning
confidence: 99%
“…For instance, Guo and Miller [2] found that new ventures with good guanxi with the government may enhance their ability to access entrepreneurial resources and be more confident in doing business in China. Using a sample of 55 biopharmaceutical high-tech firms in China, Wang and Lestari [26] precisely pointed out that government guanxi is positively related to market entry success because the Chinese government "has the authority to approve projects, allocate resources, and arrange financing and distribution."…”
Section: Guanxi Strategy Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that recent policy changes have formalized the legitimacy of private ownership and publicly ordered that it be treated on the same basis as state-owned enterprises, state banks are still reluctant to give them loans (The Economist, 2002;Yang, 2002;Guo and Miller, 2010;He, 2009). This inhibits the opportunity for these entrepreneurs to invest in new technologies, to innovate and to fully exploit emerging market opportunities.…”
Section: The Emergence Of Entrepreneurs In the Private Sectormentioning
confidence: 99%
“…The characteristics of these personal networks are the very reason guanxi has been such a necessary and important factor of production in the Chinese economy. A growing number of studies have shown that it is unavoidable for Chinese companies' entrepreneurial activities to be imbedded in a guanxi network Yeung and Tung 1996;Yu et al 2013;Guo and Miller 2010;Liao and Sohmen 2001;Yang and Jiang 2010;Arribas et al 2012;Puffer et al 2010;Lovett et al 1999;Yang and Wang 2011).…”
Section: Introductionmentioning
confidence: 99%